The 2018 AACC/SYCL PhD Clinical Chemist Compensation Survey. (4th March 2020) - Bunch, Dustin R; El-Khoury, Joe M; Colby, Jennifer; Colon-Franco, Jessica; Hackenmueller, Sarah A; Olson, Kalen N; Cotten, Steven W; Kampfrath, Thomas; Chittiprol, Seetharamaiah; Suh-Lailam, Brenda; French, Deborah; Isbell, T Scott; et al.
Abstract: Background: Doctoral level board-certified clinical chemists play an invaluable role in many facets of laboratory medicine and healthcare. However, information concerning their total compensation is sparse. Content: A confidential self-reported compensation survey was conducted by the American Association for Clinical Chemistry's Society for Young Clinical Laboratorians (AACC SYCL) Core Committee from April 1 to April 17, 2018. Respondents provided information on geographic location, employment sector, gender, and years of experience to account for the influence of these variables on compensation. There were 199 respondents in total from the United States and Canada, however, only respondents employed in the United States with an earned doctoral degree and certification by the American Board of Clinical Chemistry ( n = 133), were included in the full analysis. In comparison to compensation reported in AACC SYCL salary surveys conducted in 2010 and 2013, early career median salaries are trending upwards after correction for inflation. Summary: This survey is the first to collect the gender of respondents, and identify a pay gap for some geographic groups. However, this gap could be due in part to a difference in the years of experience, since males were highly represented in the group with >20 years of experience (25 out of 35, 71%). Future studies on compensation trends within clinical chemistry that do not rely on self-report are needed to ensure accuracy and completeness of the dataset.